Demographic outline of people of Jammu and Kashmir - Hussain, Sarfraz; Sharma, Geetu (Innovative Research Thoughts, 2017)
Jammu and Kashmir is an Indian state with a unique cultural character. As it shares the international border with Pakistan and China, the State has a dominating position. The grandeur of snow-capped mountains, huge natural lakes, woods, rivers and springs enriches it. It consists of three major natural areas, Jammu, Kashmir and Ladakh. The state, however, is split into two major divisions for administrative purposes: Cashmir with eight districts, including two districts in Ladakh, and Jammu with six districts. The trend of Jammu and Kashmir development is not promising. It has lagged behind other countries in terms of net domestic product (NSDP) growth at current prices.